2017
DOI: 10.1186/s13054-017-1633-1
|View full text |Cite
|
Sign up to set email alerts
|

Duration of veno-arterial extracorporeal life support (VA ECMO) and outcome: an analysis of the Extracorporeal Life Support Organization (ELSO) registry

Abstract: BackgroundVeno-arterial extracorporeal membrane oxygenation (VA ECMO) is an effective rescue therapy for severe cardiorespiratory failure, but morbidity and mortality are high. We hypothesised that survival decreases with longer VA ECMO treatment. We examined the Extracorporeal Life Support Organization (ELSO) registry for a relationship between VA ECMO duration and in-hospital mortality, and covariates including indication for support.MethodsAll VA runs from the ELSO database from 2002 to 2012 were extracted.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
132
2
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(152 citation statements)
references
References 31 publications
4
132
2
5
Order By: Relevance
“…An Extracorporeal Life Support Organization (ELSO) data analysis indicated that the best survival was observed with venoarterial ECMO weaning at support day 4. A shorter duration was associated with higher mortality, most likely because of inadequate support, and a gradually decreasing survival from 4 to 12 days of assistance was also observed with a constant low survival beyond the second week of cardiorespiratory support.…”
Section: Discussionmentioning
confidence: 99%
“…An Extracorporeal Life Support Organization (ELSO) data analysis indicated that the best survival was observed with venoarterial ECMO weaning at support day 4. A shorter duration was associated with higher mortality, most likely because of inadequate support, and a gradually decreasing survival from 4 to 12 days of assistance was also observed with a constant low survival beyond the second week of cardiorespiratory support.…”
Section: Discussionmentioning
confidence: 99%
“…The number of VA‐ECMO cases has increased fourfold between 2010 and 2015 establishing its central role in the management of cardiogenic shock . However, outcomes remain poor with a 41% survival to discharge and no clear trend toward improvement . In an effort to reduce waitlist mortality, the new UNOS organ allocation policy has given patients supported on VA‐ECMO Tier 1 (highest priority) status and is therefore likely to render urgent HT from VA‐ECMO as a feasible option at centers where long wait times previously precluded this approach.…”
Section: Discussionmentioning
confidence: 99%
“…Venoarterial extracorporeal membrane oxygenation (VA‐ECMO) provides temporary circulatory support for patients in refractory cardiogenic shock. While its use has increased exponentially over the past decade, outcomes have not followed the same trajectory . Heart transplant (HT) from VA‐ECMO is a feasible option as demonstrated in the pediatric population and in countries where these patients are given high priority status .…”
Section: Introductionmentioning
confidence: 99%
“…Its use is increasing but survival to hospital discharge remains between 50 and 60% [2]. Older age, being immunocompromised, longer duration of mechanical ventilation before vv-ECMO, neuromuscular blockade agents, nitric oxide use and increased extra-pulmonary organ failure are associated with worse outcomes [3–5].…”
Section: Introductionmentioning
confidence: 99%